The Impact of Total Quality Management on the Quality of Institutional Performance in Saudi Hospitals: A Case Study of King Faisal Hospital - Saeed Okour, Karim (International Journal of Psychosocial Rehabilitation, 2020)
Here is the main goal and the first is to reach the levels of excellence without applying the health quality management system, but that its application here is carried out with that individual image and at the present time there are some initiatives to present and improve the health quality management system through working on the application of the five levels of maturity, so the goal returns The basic here in the research is to reach the design of those levels that exist and examine the maturity level in the health quality management in service organizations, to serve as a guide for senior management to assess that level of maturity in performance, and King Faisal Hospital has also been chosen. Makkah, Saudi Arabia, and it became clear from the results of the application of the examination list that the hospital got a maturity level for quality management with an average of 2.985, and it is thus at the beginning of the second maturity level (organizational management), which indicates here that that hospital administration carries out and carries out many operations and activities in Different levels; therefore, the hospital’s senior management should strive to start implementing a quality assurance or implementing an ISO 9001:2008 quality management system to reach the third level of maturity, which is the desired level.